Engaging Junior High School Students in Speaking Skills Through Digital Storytelling - -, Dina Nailatur Rohmah (Universitas Nahdatul Ulama Surabaya, 2022)
Abstract: Speaking is one of the language skills in daily life. The people more often choices to speaking in communication, because the communication more effective by talking or speaking. Speaking is very important in life. This makes speaking skills must be considered and developed properly, of course by using a good way and method. With this skill, a person can convey ideas or thoughts that can be understood by others. Therefore, there needs a learning method that can help someone, especially students in handling it. The combination of methods with skills can make it easier for students to develop and increase knowledge in speaking, especially in English. Digital Storytelling is a method that is starting to develop at this time, because of the coved 19 pandemics that occurred in various countries, then this method is very functional in the development of student skills. Therefore, this study aims to analyze whether the Digital Storytelling method can influence the development of speaking skills in students. This study was conducted on 8th graders. The data collection is done with, teacher interviews, learning video analysis, and student videos that have been done. The research method used is a qualitative method with a focus on the study case, so it can be analyzed that this method can make a good contribution to the development of student speaking skills in eighth grade at junior high school.